The Role of Leadership Style, Work Environment, and Compensation on Employee Performance at PT. PDAM Tirta Moedal Semarang City - Kasturi, Dila Nor; Panjaitan, Roymon (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
In the development of the business world, high-quality and professional human resources are crucial for companies. This study aims to determine how leadership style, work environment, and compensation affect employee performance at PT. PDAM Tirta Moedal, Semarang City. The data collection technique used in this research is a quantitative approach through the distribution of questionnaires. The sampling method applied is purposive sampling, with a total of 100 respondents. Data analysis was conducted using Smart PLS version 4 software, employing both outer model and inner model analysis. The results of the study indicate that the work environment and compensation have a significant influence on employee performance, while leadership style has a positive but not significant effect. By establishing clear and measurable standard operating procedures as a reference for employee performance, this study identifies high-quality human resources capable of improving overall employee performance. Keywords: leadership style; work environment; compensation; employee performance. Pada perkembangan dunia bisnis, sumber daya berkualitas tinggi dan profesional sangat penting bagi perusahaan. Studi ini bertujuan untuk menguji pengaruh gaya kepemimpinan, lingkungan kerja, dan kompensasi terhadap kinerja karyawan di PT. PDAM Tirta Moedal Kota Semarang. Teknik pengumpulan data pada penelitian ini adalah pendekatan kuantitatif dengan menggunakan kuesioner. Metode dalam pengambilan sampel menggunakan purposive sampling dengan 100 responden. Teknik analisis menggunakan software Smart PLS versi 4.0 dengan analisis outer model dan inner model. Hasil studi menyatakan lingkungan kerja serta kompensasi berpengaruh signifikan terhadap kinerja karyawan, sedangkan gaya kepemimpinan berpengaruh positif namun tidak signifikan. Dengan membuat standar operasional yang jelas dan dapat diukur sebagai acuan kinerja karyawan, sumber daya berkualitas tinggi yang dapat meningkatkan kinerja karyawan dapat ditemukan melalui studi ini. Kata kunci: gaya kepemimpinan; lingkungan kerja; kompensasi; kinerja karyawan.